Новітні тенденції у методологічних підходах щодо оцінки продовольчої безпеки країни - Нестеренко, Світлана Анатоліївна; Нестеренко, Светлана Анатольевна; Nesterenko, Svitlana (ХНАУ, 2016)
UK: В статті обґрунтовано соціально-економічну й геополітичнe сутність продовольчої безпеки з точки зору її багаторівневості. Проаналізовано особливості продовольчої безпеки у рівневому – просторовому вимірі й досліджено основні критерії її оцінки. RU: В статье обосновано социально-экономическую и геополитическую сущность продовольственной безопасности с точки зрения ее многоуровневости. Проанализированы особенности продовольственной безопасности в уровневом пространственном измерении и исследованы основные критерии ее оценки. EN: The need for food security as a component of economic security arises in connection with the protection of public interest, such as social stability, meet the nutritional needs independence from imports, the development of domestic production of food products, the creation of reserve stocks to stabilize food security. The main criteria of food security is the ability of countries to provide the population with food at complete self-sufficiency. In accordance with the strategic directions of development of agriculture of Ukraine till 2020 the aim of the development strategy of the agricultural market and its infrastructure is to develop effective mechanisms of agricultural products and processed products, providing expanded reproduction of production, timely supply and effective implementation of marketing channels, and availability and adequacy of food for all the population. This strategic objective is ensuring food independence for certain products, namely achieving a safe ratio between the volume of imports of a particular product in kind and capacity of its domestic market. Considering it extremely important to establish a national model of food security, which should contribute to providing the population with safe and quality food, stability of domestic food production, the amount of which would be sufficient to ensure food independence on conditions for access to the consumption of the vast majority of even the richest segments of population.
Новейшие тенденции в методологические подходы к оценки продовольственной безопасности страны
Latest trends in methodological approaches to assess food security
Keywords: агропродовольчий ринок; продовольча безпека; забезпечення; життєдіяльність людини; продукти харчування; зовнішнє середовище; агропродовольственный рынок; продовольственная безопасность; обеспечение; жизнедеятельность человека; продукты питания; внешняя среда; agri-food market; food safety; security; human activity; food; environment